2004
DOI: 10.3354/ame037265
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on respiration and photosynthesis in three diatom-dominated benthic communities

Abstract: Short-term temperature effects on respiration and photosynthesis were investigated in intact diatom-dominated benthic communities, collected at 2 temperate and 1 high-arctic subtidal sites. Areal rates of total (TOE) and diffusive (DOE) O 2 exchange were determined from O 2 -microsensor measurements in intact sediment cores in the temperature range from 0 to 24°C in darkness and at 140 µmol photons m -2 s -1 . In darkness, the O 2 consumption increased exponentially with increasing temperature for both TOE and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
113
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 48 publications
17
113
2
Order By: Relevance
“…The temperature range observed here (14 -28°C) is modest (Table 1) and a temperature effect on BPP is obscured by the dominant response to variability in PAR flux. The absence of strong temperature dependence in our regression analysis is consistent with the results of Hancke and Glud [2004] for temperate and arctic benthic photosynthesis and Behrenfeld and Falkowski [1997] for planktonic autotrophs. Both studies observed a broad maximum in photosynthetic response with respect to temperature, with a decrease in response at the highest temperatures surveyed.…”
Section: Benthic Particulate Organic Matter and Chl Asupporting
confidence: 78%
“…The temperature range observed here (14 -28°C) is modest (Table 1) and a temperature effect on BPP is obscured by the dominant response to variability in PAR flux. The absence of strong temperature dependence in our regression analysis is consistent with the results of Hancke and Glud [2004] for temperate and arctic benthic photosynthesis and Behrenfeld and Falkowski [1997] for planktonic autotrophs. Both studies observed a broad maximum in photosynthetic response with respect to temperature, with a decrease in response at the highest temperatures surveyed.…”
Section: Benthic Particulate Organic Matter and Chl Asupporting
confidence: 78%
“…The microphytobenthos is usually limited to the surface 2 or 3 mm of sediment, therefore high resolution measurements are required; photosynthesis is measured to a resolution of 100 m and the sensing tips of the microelectrode have diameters of only 2 -10 m (Revsbech et al, 1989). While oxygen microelectrodes just measure oxygen concentration, it is possible to measure gross photosynthesis rates using the light-dark shift method (Revsbech & Jørgensen, 1983;Glud et al, 1992;Lassen et al, 1998;Hancke & Glud, 2004). Moreover, oxygen concentration profiles can be used to calculate respiration and net photosynthesis rates according to Kühl et al (1996) and Hancke & Glud (2004) based on Fick's first law of diffusion.…”
Section: Gas Exchange Methodsmentioning
confidence: 99%
“…While oxygen microelectrodes just measure oxygen concentration, it is possible to measure gross photosynthesis rates using the light-dark shift method (Revsbech & Jørgensen, 1983;Glud et al, 1992;Lassen et al, 1998;Hancke & Glud, 2004). Moreover, oxygen concentration profiles can be used to calculate respiration and net photosynthesis rates according to Kühl et al (1996) and Hancke & Glud (2004) based on Fick's first law of diffusion. Estimates of benthic primary productivity are also made using oxygen exchange across the sediment-water interface using benthic chambers or sediment cores (Thornton et al, 2002).…”
Section: Gas Exchange Methodsmentioning
confidence: 99%
“…In this study, we have observed that benthic respiration could be driven by quantitative changes in labile fraction of sedimentary organics throughout the year. However, Ní Longphuirt et al (2007) and Ferrón et al (2009a) observed in other coastal areas that benthic respiration was not related to temperature or total organic matter, notwithstanding changes in both these variables could induce alterations in heterotrophic processes (Hancke and Glud, 2004).…”
Section: Benthic Fluxesmentioning
confidence: 99%